2013
DOI: 10.1186/1472-6963-13-117
|View full text |Cite
|
Sign up to set email alerts
|

Is Europe putting theory into practice? A qualitative study of the level of self-management support in chronic care management approaches

Abstract: BackgroundSelf-management support is a key component of effective chronic care management, yet in practice appears to be the least implemented and most challenging. This study explores whether and how self-management support is integrated into chronic care approaches in 13 European countries. In addition, it investigates the level of and barriers to implementation of support strategies in health care practice.MethodsWe conducted a review among the 13 participating countries, based on a common data template inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
148
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(154 citation statements)
references
References 41 publications
5
148
0
1
Order By: Relevance
“…Of the people with diabetes and identified as potentially eligible in the electronic medical records of the 18 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the people with diabetes and identified as potentially eligible in the electronic medical records of the 18 …”
Section: Resultsmentioning
confidence: 99%
“…16 17 Although the concept of a collaborative approach is widely acknowledged, it is not yet an integral part of daily practice. 18 Decision aids or support systems can encourage patient-provider discussions about disease management by presenting available treatment options and expected outcomes for each patient. 19 Most aids, however, focus on one specific treatment choice, whereas people with diabetes are often confronted with multiple clinical domains (glucose, blood pressure, lipids) for which treatment is indicated.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research demonstrates that selfmanagement support continues to be the most challenging aspect of care to enact within the context of the PHC care team (Elissen et al, 2013).…”
Section: Self-management Supportmentioning
confidence: 99%
“…The findings of this study are not typical for the Netherlands alone. A qualitative study conducted by Elissen and colleagues 34 showed that self-management support for patients with chronic diseases is far from adequate in most European countries, and that approaches to such support appear to be the least implemented and most challenging among the elements of the Chronic Care Model. 35 These findings emphasize the need for a better understanding of how we can encourage patients and health care professionals to engage in productive interactions, thereby improving mental and physical quality of life outcomes.…”
Section: Self-management and Quality Of Lifementioning
confidence: 99%